2015
DOI: 10.1016/j.jes.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bisphenol A (BPA) neurotoxicity in vitro with mouse embryonic stem cells

Abstract: The adverse effects of environmental pollution on our well-being have been intensively studied with many in vitro and in vivo systems. In our group, we focus on stem cell toxicology due to the multitude of embryonic stem cell (ESC) properties which can be exerted in toxicity assays. In fact, ESCs can differentiate in culture to mimic embryonic development in vivo, or specifically to virtually any kind of somatic cells. Here, we used the toxicant Bisphenol A (BPA), a chemical known as a hazard to infants and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…However, BPA is still being used as part of the plastic containers for embryo cultures (Hunt et al 2003, Berger et al 2010, Varayoud et al 2011). Studies indicated a broad range of effects on the embryos upon BPA exposure, such as altered developmental rate and cell death (Ferris et al 2016) and toxicity to the neural progenitor cells (Yin et al 2015). BPA-free replacement products from the industry still diffuse out estrogenic chemicals, such as BPAF (the fluorinated form of BPA) (Bittner et al 2014), which may pose a significant hazard to the embryos.…”
Section: Environmental Exposuresmentioning
confidence: 99%
“…However, BPA is still being used as part of the plastic containers for embryo cultures (Hunt et al 2003, Berger et al 2010, Varayoud et al 2011). Studies indicated a broad range of effects on the embryos upon BPA exposure, such as altered developmental rate and cell death (Ferris et al 2016) and toxicity to the neural progenitor cells (Yin et al 2015). BPA-free replacement products from the industry still diffuse out estrogenic chemicals, such as BPAF (the fluorinated form of BPA) (Bittner et al 2014), which may pose a significant hazard to the embryos.…”
Section: Environmental Exposuresmentioning
confidence: 99%
“…In utero exposure to BPA in mice was shown to reduce dendritic spine densities in the hippocampal CA1 region, regardless of its dose [82]. BPA was demonstrated to impair neural ectoderm specification and neural progenitor cells in mouse embryonic stem cells [83]. In a study using Caenorhabditis elegans to examine early embryogenesis exposure to BPA and BPS into adulthood, it was shown that changes in behavior and learning were followed into adulthood [84].…”
Section: Epidemiologic and Experimental Evidence Of Brain Health Dmentioning
confidence: 99%
“…BPA would enter into the environment by the industrial emissions, the disposal of PVC materials, and the using process of the products containing BPA . BPA has toxic effect on the reproductive system and nervous system of biological organisms . Besides, BPA has certain affinity with estrogen receptor , which can lead to the occurrence of ovarian cancer, breast cancer, and other cancers.…”
Section: Introductionmentioning
confidence: 99%